(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, information on improving the knowledge of primary school students in their native language and forming independent creative thinking skills, the problems of developing talent, the problems of developing interest in various forms of activity, and information is given.